Modern Trends in Public Funding of Higher Education - M. De Martino; G. F. Tkach; S. A. Kovalenko (Высшее образование в России)
Public funding currently plays a key role in the stability and success of higher education systems in the world leading countries. As governments are often the main sources of funding for higher education, the effectiveness of public policies in allocating financial flows is a matter of concern. This paper discusses the main mechanisms of financing higher education systems and analyzes the structures and features of these mechanisms using the examples of the largest countries of Western Europe and Asia – Germany, Spain, Italy, France, and China.Materials and methods. In order to identify current trends in public funding of higher education, the authors used two main groups of materials, which can be conditionally divided into official regulatory documents and statistical (analytical) reviews. Systemic-structural and statistical data analysis methods were applied in the research.Results. The study of trends in public funding of higher education revealed their great diversity not only in terms of the share in the overall structure of university income, but also in the mechanisms of distribution of financial flows. Nevertheless, this study presents the main groups of these mechanisms, structured according to the methods of their implementation.Discussion and Conclusion. In the course of the study, the authors concluded that the existing diversity of the world’s higher education financing systems is primarily due to the sustainability of traditions that have developed in national education systems, and the lack of international initiatives aimed at unifying the mechanisms of education financing, as was done earlier on the structure, levels and qualifications in the implementation of the bologna Process. In addition, the constantly changing financial situation in the world encourages states to look for alternative sources of support for higher education, which leads to the creation of new independent financing mechanisms.